Perinatal care plan for a woman with coexisting cervical cancer - Tusiewicz, Monika M.; Szablewska, Anna W. (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Any pregnancy in which cancer is diagnosed requires comprehensive medical care that addresses the needs of both the mother and the developing foetus. This case study discusses a 37-year-old woman diagnosed with G1 cervical cancer with microinvasion during the first trimester of her second pregnancy. The patient received chemotherapy during the second and third trimesters, and the pregnancy was terminated by elective caesarean section at 37 weeks of gestation. The aim of this study is to identify the nursing problems encountered by a pregnant and postpartum woman with coexisting cervical cancer. The care plan was based on a holistic and individualised approach, utilising ICNP ® terminology, C-HOBIC indicators, and the EPDS scale. The midwife’s care focused on improving the patient’s comfort, providing mental health support, and offering education on the disease, treatment, postpartum care, and newborn care.